DIVIDEND POLICY AND FINANCIAL PERFORMANCE OF QUOTED OIL AND GAS COMPANIES IN NIGERIA - Ajose Kehinde Gabriel (Malete Journal of Accounting and Finance)
Dividends are payments made by a company to its shareholders to compensate them for the unforeseen risk they decided to undertake and for the time value of their investment in the organisation This study examined the impact of dividend policy (DP) on the financial performance of oil and gas in Nigeria. The study employed exploratory research design. Six (6) listed oil and gas companies were chosen through a purposive sampling technique and data extracted from the annual reports of these oil and gas from year 2009 to 2021. A panel data regression was used to analyse the data. Dividend policy was proxies with dividend per share (DPS), leverage (LEV), liquidity (LIQ), Earnings per share (EPS), and risk (RISK) while financial performance was proxies with Return on Equity (ROE) and Return on Asset (ROA). Findings revealed that the variable- leverage (LEV), earnings per share (EPS), risk (RISK) has statistical significant effect on the Return on Asset (ROA) while Dividend per share (DPS) and liquidity (LIQ) have negative and significant impact on Return on Asset (ROA). Results also, show that the variable- leverage (LEV), earnings per share (EPS), risk (RISK) has statistical significant effect on the Return on Asset (ROE) while Dividend per share (DPS) and liquidity (LIQ) have negative and significant impact on Return on Asset (ROE). It was concluded that dividend policy had negative significant impact on return on asset and return on equity. The study recommended that, the company would pay no dividend. They would retain all earnings to maximise market price per share since they can earn more on investment than share holder expectation.